2014
DOI: 10.1002/ange.201403288
|View full text |Cite
|
Sign up to set email alerts
|

Practical, Modular, and General Synthesis of Benzofurans through Extended Pummerer Annulation/Cross‐Coupling Strategy

Abstract: Operationally simple, efficient, and widely applicable Pummerer annulations of simple phenols with ketene dithioacetal monoxides, with the aid of trifluoroacetic anhydride, have been shown to provide a variety of benzofurans having a methylthio group at the 2-position. Subsequent and newly developed nickel-catalyzed arylation at the methylthio group culminates in diversity-oriented synthesis of multisubstituted benzofurans. Our extended Pummerer annulation/ cross-coupling sequence is powerful enough to synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Based upon our previous and present experimental observations, we propose that an interrupted Pummerer reaction to form I or II , via addition of oxygen of phenols 2 (refs 42, 43, 46) or S E 2′ addition of the silanes 5 (refs 34, 35, 45) and 7 (refs 36, 37, 38) to the sulfur of activated benzothiophene S -oxide III , precedes a charge accelerated [3,3]-sigmatropic rearrangement, resulting in complete regioselective C–C bond formation at the expense of a C–H bond (Fig. 2).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Based upon our previous and present experimental observations, we propose that an interrupted Pummerer reaction to form I or II , via addition of oxygen of phenols 2 (refs 42, 43, 46) or S E 2′ addition of the silanes 5 (refs 34, 35, 45) and 7 (refs 36, 37, 38) to the sulfur of activated benzothiophene S -oxide III , precedes a charge accelerated [3,3]-sigmatropic rearrangement, resulting in complete regioselective C–C bond formation at the expense of a C–H bond (Fig. 2).…”
Section: Resultsmentioning
confidence: 62%
“…Recently, we34353637383940 and others41424344454647484950515253545556 reported the metal-free, sulfoxide directed57 C–H functionalization of a variety of molecular scaffolds, which was enabled by an interrupted Pummerer reaction28. Spurred on by these recent achievements, we considered the use of benzothiophene S -oxides 1 for the synthesis of important C3-functionalized benzothiophenes, as the corresponding sulfonium salts I and II , formed after reaction with the coupling partners, lack aromaticity about the five-membered ring and should therefore undergo facile C–C bond formation via [3,3]-sigmatropic rearrangement58, thus delivering unexplored reactivity not accessible in benzothiophenes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening reaction conditions, we found that trifluoroacetic anhydride (TFAA) is the best activator that allows various KDMs to engage in the annulation (Scheme 14). [23] Under the second-generation conditions, unsubstituted, alkyl-substituted, and aryl-substituted KDMs participated to afford 25 a-h in high yields. The scope of phenols is as wide as that in Scheme 12: A variety of functional groups in 25 k-n were compatible and the annulation was regioselective for meta-or ortho-substituted phenols.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…[2] In contrast, the development of new reactions of aryl sulfides has only been reported only scarcely.T ransition-metalcatalyzed cross-coupling reactions of aryl sulfides [3] are difficult to achieve because sulfur species can permanently poisont he catalysta nd C(sp 2 )ÀSb onds are rather strong and difficult to cleave. To overcome these difficulties, reactive Grignardr eagents were employed as nucleophiles [4] or aryl sulfides were used that have special structures that facilitate efficient conversion. [5][6][7] We are interested in catalytic transformationso fo rganosulfur compounds [4e-g, 8] and recently developed general cross-coupling reactions of aryl sulfides with arylzinc reagents by using ap alladium-NHC complex as catalyst.…”
mentioning
confidence: 99%